The Associations of Anaemia Status and Body Mass Index with Asthma Severity in Saudi Arabia: A Comparative Study - Bugis AA; Bugis B; Alzahrani A; Alamri AH; Almalki HH; Alshehri JH; Alqarni AA; Turkestani FA (Journal of Asthma and Allergy, 2025)
Alaa A Bugis,1– 3 Bussma Bugis,4 Abdulsalam Alzahrani,1– 3 Ali Hasan Alamri,1– 3 Hamad Hani Almalki,1– 3 Jamal Hassan Alshehri,1– 3 Abdullah Ali Alqarni,1– 3 Faisal A Turkestani1– 3,5 1Respiratory Therapy Program, College of Applied Medical Sciences, King Saud bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia; 2Research Office, King Abdullah International Medical Research Center, Jeddah, Saudi Arabia; 3Respiratory Therapy Department, Ministry of National Guard Health Affairs- King Abdulaziz Medical City, Jeddah, Saudi Arabia; 4Department of Public Health, College of Health Sciences, Saudi Electronic University, Dammam, Saudi Arabia; 5Echo Cardiovascular Technology Department, College of Applied Medical Sciences, King Saud bin Abdulaziz University for Health Sciences, Jeddah, Saudi ArabiaCorrespondence: Faisal A Turkestani, Respiratory Therapy Program, College of Applied Medical Sciences, King Saud bin Abdulaziz University for Health Sciences, P.O. Box 9515, Jeddah, 21423, Saudi Arabia, Tel +966122246134, Email turkestanif@ksau-hs.edu.saPurpose: This study aimed to investigate the associations of anaemia status and body mass index (BMI) with asthma severity in adult subjects.Methods: The study included 300 adults who had asthma and admitted to King Abdulaziz Medical City from about 2017 to 2022. The subjects’ demographic data, BMI, anaemia status, and number of asthma-related hospital admissions were analyzed. Associations between anaemia, BMI, and asthma severity were investigated within a cross-sectional comparative design. Anaemia status as well as BMI variations may have an impact on the frequency of asthma-related hospitalizations.Results: Most subjects in the study were female (74.3%) and over the age of 65. Mild anaemia was the most common condition (41.7%), and (42.3%) of subjects were classified as obese and (22.7%) were overweight. Age was found to be a significant factor in asthma-related hospital admissions (p-value = 0.0002), however sex was not significant. Subjects with mild or moderate anaemia and those who were obese had a higher frequency of asthma-related hospital admissions. Furthermore, the study revealed significant differences in the mean number of asthma-related hospital admissions among the different BMI and anaemia status categories. Subjects with severe obesity had a significantly greater number of asthma-related hospital admissions with a mean of 2.21 compared with the other BMI groups (p-value= 0.029). Subjects with mild anaemia had a significantly greater number of asthma-related hospital admissions with a mean of 2.07 than those with severe anaemia (p-value=0.04). These results highlight the importance of considering comorbid conditions in the clinical assessment and management of asthma.Conclusion: These findings highlight that anemia and BMI abnormalities can complicate asthma management. Health care professionals should be aware of these factors when assessing severity and developing treatment plans. Further research is needed to explore the underlying mechanisms and evaluate interventions targeting anaemia and BMI to improve outcomes.Keywords: asthma, exacerbation, airway hyperresponsiveness, anaemia, iron deficiency, body mass index, BMI